Impact of Covid-19 Social Restrictions on Seafood Culinary-Based Tourism Industry at Kampung Solor - Nugraha, Yudha Eka (Media Wisata, 2023)
The impact of the COVID-19 pandemic has occurred in various sectors, one of which is the culinary industry. This study aims to identify the impact of COVID-19 social restrictions on the seafood-based tourism industry at the Solor Village Night Market. Using qualitative methods, research informants were selected by purposive sampling technique, which resulted in as many as 24 culinary business unit owners becoming research participants. Data collection techniques were carried out, starting with observation, interviews, and documentation. The results of this study indicate that: (1) COVID-19 social restrictions are implemented evenly throughout Indonesia, including in East Nusa Tenggara Province, so that people are more active at home. (2) There are at least two impacts of the pandemic that were felt by the culinary business unit managers at the Solor Village Night Market, namely the impact on the decline in income and job opportunities. (3) The impact of the COVID-19 social restrictions on the decrease in the income of the culinary business unit managers is influenced by several factors, such as the decline in people's purchasing power and the tendency to stay active at home so that economic activity is not optimal. (4) The impact of the pandemic on job opportunities was felt by the employees of the culinary business unit at the Pasar Malam Kampung Solor who rely on their daily wage income to support education, where as many as more than 50% of the employees were laid off. The next recommendation for business unit managers is to be able to use social media as an alternative promotion tool to maintain income in times of crisis.